Comparison of conventionally performed and electroanatomic mapping system guided catheter ablation for AV nodal reentrant tachycardia - prospective single-centre study. (24th May 2021) - Dorottya, D; Janosi, K; Vilmanyi, G; Simor, T; Kupo, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Radiofrequency (RF) catheter ablation in atrioventricular nodal reentry tachycardia (AVNRT) is highly effective. Three-dimensional electroanatomic mapping system (EAMS)-guided procedures are becoming more widespread. Purpose: We aimed to compare EAMS-guided procedures to conventionally, only-fluoroscopy approach for slow pathway ablation. Methods: 152 patients undergoing electrophysiological study and slow pathway ablation due to documented AV nodal reentrant tachycardia were included in our prospective single-centre study. In 102 patients the procedure was performed conventionally (Group 1) and 50 patients underwent an electroanatomic mapping system (EAMS) -guided approach (Group 2). Results: In Group 2, 80% of the procedures were performed without the use of radiation. The procedure time (median (interquartile range): 65 (50-84) min vs. 75 (60-96.3) min, p =0.005) was significantly shorter in Group 1, with longer fluoroscopy time (4.2 (2.4-7.9) min vs. 0 (0-0) min, p < 0.001). There was no difference either in the number of RF applications (mean ± standard deviation 10.8 ± 8.5 vs. 10.2 ± 7.7, p = 0.66) or in the ablation time (297 ± 237 s vs. 294 ± 196 s, p = 0.74). All patients were treated successfully. One recurrence occurred in each groups during the follow-up. Conclusions: In our series, EAMS-guided approach for slow pathway ablation was associated with reduced fluoroscopy and longer procedure time compared to conventional, only-fluoroscopy approach. No difference was found in ablation time, success rate or recurrence.